From objective to constituted risk: an alternative approach to safety in strategic technological innovation in the European Union. Issue 1 (2nd January 2016) - Rodríguez, Hannot
Abstract : Safety is a legitimate means of limiting technological innovation in our societies. However, the potential socio-economic impact of curtailing techno-industrial progress on the grounds of safety means that risk governance policies tend to restrict the range of legitimate approaches to safety on the principle that it can only be discussed in the frame of an allegedly objective scientific representation of risk. In European risk governance, socio-economic factors such as the underlying innovation rationales and goals are not openly considered to be related to the constitution of safety, but tend largely to be treated as factors of subjective reaction towards risk and technology. This paper seeks to overcome that approach by proposing a 'constitutive' understanding of how risk and socio-economic factors and dynamics relate, focusing in particular on the 'safe and responsible' development of nanotechnology in the European Union (EU). I argue that risk is constituted according to socio-economic considerations, and that the controllability of the environmental and health risks of nanotechnology in the EU is assumed on principle in the very strong institutional commitment to the industrial exploitation of nanotechnology R&D. Using a constitutive approach, we may legitimately conceive a broader set of potential safety scenarios, while at the same time highlighting major obstacles to implementing more critical constitutions of techno-industrial risk in the framework of a highly competitive knowledge-based global economy.